Controlling Organisasi Dalam Perspektif Al-Qur’an Dan Hadits - Endah Tri Wisudaningsih (HUMANISTIKA : Jurnal Keislaman, 2018)
Controlling, whether in terms of supervision or control by most societies, is often interpreted as an attempt by a manager or supervisory agency as an activity to find fault. In fact, if carefully understood, the function of supervision or control is actually as one of the strengths to make improvements if the results or services that have been standardized is not in accordance with the expected results. Standardization is one of the initial actions of the planning process and that standard must be reliable and reliable as a basis for evaluating and comparing through surveillance activities. Standardization of the planning process is intended for the achievement of organizational goals or effectiveness, while supervision is more focused on the implementation process and the results of productivity, both in the form of goods or services. Monitoring efforts should be maximized so that the business results of an organization is more efficient.